Molecular Mechanisms Controlling Foxp3 Expression in Health and Autoimmunity: From Epigenetic to Post-translational Regulation - Colamatteo, Alessandra; Carbone, Fortunata; Bruzzaniti, Sara; Galgani, Mario; Fusco, Clorinda; Maniscalco, Giorgia Teresa; Di Rella, Francesca; de Candia, Paola; De Rosa, Veronica (Frontiers in Immunology, 2020)
The discovery of the transcription factor Forkhead box-p3 (Foxp3) has shed fundamental insights into the understanding of the molecular determinants leading to generation and maintenance of T regulatory (Treg) cells, a cell population with a key immunoregulatory role. Work over the past few years has shown that fine-tuned transcriptional and epigenetic events are required to ensure stable expression of Foxp3 in Treg cells. The equilibrium between phenotypic plasticity and stability of Treg cells is controlled at the molecular level by networks of transcription factors that bind regulatory sequences, such as enhancers and promoters, to regulate Foxp3 expression. Recent reports have suggested that specific modifications of DNA and histones are required for the establishment of the chromatin structure in conventional CD4+ T (Tconv) cells for their future differentiation into the Treg cell lineage. In this review, we discuss the molecular events that control Foxp3 gene expression and address the associated alterations observed in human diseases. Also, we explore how Foxp3 inﬂuences the gene expression programs in Treg cells and how unique properties of Treg-cell subsets are deﬁned by other transcription factors.